An in-depth investigation into the safety of Nyanga's public spaces from a gender-sensitive perspective. - Mofokeng, Tiisetso (School of Architecture, Planning and Geomatics, 2023)
Historically - and currently - women in the global South have generally been viewed as subordinate to men. This is often centred around social perceptions of the different genders and is especially apparent in modern-day leadership, policymaking and managerial roles, where roles are often set aside for men. In the Cape Town township of Nyanga, three public spaces have been identified as crime hotspots. Women who live in the area do not feel safe in these spaces and are often the victims of crime. Thus, there is a need for an in-depth, gender-sensitive investigation into the safety of Nyanga's public spaces. This study seeks to do this and to explore how and why Nyanga's public spaces are failing to deliver gender-sensitive safety outcomes. Methodologically, the aim and main research question of the study is geared towards answering “how” and “why” questions, which necessitate a qualitative (case study and ethnographic research) approach. The tools that are used to collect such data are interviews, observations and mapping as well as Instagram question polls. The results of this study show that in order to provide safe gendersensitive outcomes, appropriate spatial interventions and safety tools need to be implemented for public spaces in Nyanga. Going forward, knowledge from this research recommends planning interventions and design resolutions that encourage South African planners and other built environment practitioners to incorporate gender-sensitive inventions in their thinking and practices. Above all else, this knowledge is geared towards empowering women by not confining them to the indoor realm of the household, but empowering them to reclaim their rights to public spaces.